The Social Role of The Faculty of Educational Sciences as Perceived by Faculty Members at Jordan University - Thaher, Amira Yousef (Journal of Educational and Psychological Sciences, 2022)
This study aimed at identifying the social role of the faculty of educational sciences by faculty at the UJ in 2021. To achieve this goal, a questionnaire is developed, which is consisted of four dimensions: Academic responsibility (teacher education), community responsibility, personal responsibility, and Community Research. The tool was distributed after verifying its validity and reliability to a randomly selected sample of 62 faculty members. The result was: the social responsibilities roles of educational faculty at JU of faculty members were high in four dimensions, with average 4.22 from 5.00. This indicates the importance of the role of faculty members in societal and social responsibilities. The results also indicated that there were no statistically significant differences attributed to the demographic variables of faculty members, except on the variable of academic rank at the dimensions of community and personal regarding professors. Also, the significant differences in dimensions academic, and community regarding faculty graduated from USA and Europe. Finally, the study recommended that: the ministry of higher education will establish an institutional work and give it great importance by adopting initiatives that serve the community in varies aspects. The College of Education should activate the role of social responsibilities in their programs and curricula.